2016
DOI: 10.1002/dys.1540
|View full text |Cite
|
Sign up to set email alerts
|

Is Reading Impairment Associated with Enhanced Holistic Processing in Comparative Visual Search?

Abstract: This study explores a proposition that individuals with dyslexia develop enhanced peripheral vision to process visual-spatial information holistically. Participants included 18 individuals diagnosed with dyslexia and 18 who were not. The experiment used a comparative visual search design consisting of two blocks of 72 trials. Each trial presented two halves of the display each comprising three kinds of shapes in three colours to be compared side-by-side. Participants performed a conjunctive search to ascertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In dyslexia research there are two opinions (Diehl et al, 2014), one as impairment in visuospatial thinking (Siok et al, 2009) and second as visuospatial strength (Brunswick et al, 2010;Wang et al, 2016). So in present study visuospatial perception is evaluated as pre-symbolic to symbolic levels (visuospatial perception, fluid reasoning and executive control), executive expression (visual discrimination, symbolic encoding for writing), perceptual processing speed (coding-digit symbols).…”
Section: 1b Visuospatial Processing and Executive Controlmentioning
confidence: 97%
“…In dyslexia research there are two opinions (Diehl et al, 2014), one as impairment in visuospatial thinking (Siok et al, 2009) and second as visuospatial strength (Brunswick et al, 2010;Wang et al, 2016). So in present study visuospatial perception is evaluated as pre-symbolic to symbolic levels (visuospatial perception, fluid reasoning and executive control), executive expression (visual discrimination, symbolic encoding for writing), perceptual processing speed (coding-digit symbols).…”
Section: 1b Visuospatial Processing and Executive Controlmentioning
confidence: 97%
“…Drawing ( f., g. Pontius, 1981;Everatt, 1997;Winner et al, 2001;Eden et al, 2003;von Károlyi and Winner, 2005;Alves and Nakano, 2014;Duranovic et al, 2015. Rudel andDenckla, 1976;Siegel and Ryan, 1989;Koenig et al, 1991;Eden et al, 1993;Everatt, 1997;Fischer and Hartnegg, 2000;Nicolson and Fawcett, 2000;von Károlyi, 2001;Winner et al, 2001;Brosnan et al, 2002;Helland and Asbjørnsen, 2003;Buchholz and McKone, 2004;Howard et al, 2006;von Károlyi and Winner, 2005;Attree et al, 2009;Brunswick et al, 2010;Facoetti et al, 2010;Collis et al, 2012;Olulade et al, 2012;Schneps et al, 2012;Alves and Nakano, 2014;Ruffino et al, 2014;Martinelli and Schembri, 2015;Wang et al, 2016.…”
Section: Global-mentioning
confidence: 99%
“…Some researchers proposed that the abstract information of three to four objects, the layout of the scene, as well as the details of the fixated object, would be maintained in the visual representation simultaneously, and the representation would not vanish in a flash and it may retain for a while even without attention, which implies that the working memory is maximally used in the comparative visual search (Hollingworth & Henderson, 2002; Irwin & David, 1992). However, others suggested that people prefer to follow a minimal working memory strategy (Ballard et al, 1997; Hayhoe et al, 1998; Wang et al, 2016), which means individuals compared the stimuli one by one to minimize the use of visual working memory. As Ballard et al (1997) reported, the online visual representation is directly relevant to the ongoing task.…”
mentioning
confidence: 99%